1978
DOI: 10.7326/0003-4819-89-6-921
|View full text |Cite
|
Sign up to set email alerts
|

Telangiectasia and von Willebrand's Disease in Two Families

Abstract: Two families are described with members who have both von Willebrand's disease and telangiectasias. Family A has four members in three consecutive generations that have both von Willebrand's disease and telangiectasias. von Willebrand's disease in this family is characterized by decreased ristocetin cofactor (FVIII-vWF), variably depressed factor VIII coagulant (FVIII-AHG), and factor VIII-related antigen (FVIII-AGN) levels. FVIII-AGN mobility on two-dimensional crossed immunoelectrophoresis was found to be no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
3

Year Published

1980
1980
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 23 publications
2
18
0
3
Order By: Relevance
“…The various abnormalities in in vitro platelet function published in the literature by several authors [12][13][14][15] have not been found neither by us nor by others [16]. No quantitative abnormali ties in von Willebrand factor ristocetin cofactor activ ity suggesting a possible von Willebrand disease could be demonstrated, although some groups have evidenced the coexistence of both pathologies in several members from a single kindred [17,18]. Von Willebrand's disease is a relatively common disease, and its association with HHT or different platelet aggregation abnormalities could have only been coin cidental.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The various abnormalities in in vitro platelet function published in the literature by several authors [12][13][14][15] have not been found neither by us nor by others [16]. No quantitative abnormali ties in von Willebrand factor ristocetin cofactor activ ity suggesting a possible von Willebrand disease could be demonstrated, although some groups have evidenced the coexistence of both pathologies in several members from a single kindred [17,18]. Von Willebrand's disease is a relatively common disease, and its association with HHT or different platelet aggregation abnormalities could have only been coin cidental.…”
Section: Discussionmentioning
confidence: 90%
“…Although the severity of bleeding is highly variable from one patient to another, in some patients, the frequent and continuous requirement of red blood cell transfusions occasionally leads to the development of secondary effects from chronic blood administration [2], No ef fective therapy has been found to stop or, at least, to lessen recurrent bleeding [2,26,27], Fragility of the vessel wall was firstly implicated in the bleeding tendency of these patients [9] but more recently, alterations in platelet function [12][13][14][15], asso ciation between HHT and von Willebrand's disease [17,18] and analytical evidence of compensated dis seminated intravascular coagulation syndrome [10], have been considered in the pathophysiology of this disorder. Fibrinolytic activators have also been impli cated in it [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric telangiopathies have also been described in association with von Willebrand's disease [19], but they are more frequently localized in the colon [20] and the finding of a platelet release defect completely differen tiates the disease [21 ]. The blue-rubber-bleb naevus syn drome has also been found with visceral involvement [22][23][24], but the usual lesion is a cavernous haeman gioma in the area of the ileo-colic artery [25].…”
Section: Case Reportmentioning
confidence: 99%
“…These may further affect the severity and the chronicity of bleeding. It has been postulated that an endothelial cell defect may result in telangiectasia and impaired production of factor VIII and vWF [28,29].…”
mentioning
confidence: 99%